Трансформація змісту дисципліни «Фізичне виховання» в умовах цифровізації вищої освіти - Нестеров, Олексій Сергійович; Лазаренко, Олександр Миколайович; Nesterov, Oleksii; Lazarenko, Oleksandr (Запоріжжя : ТДАТУ, 2026)
UA: У статті розглянуто особливості трансформації змісту дисципліни «Фізичне виховання» в умовах цифровізації вищої освіти. Проаналізовано сучасні підходи до інтеграції цифрових технологій у освітній процес, визначено їх вплив на зміну цілей, змісту, форм і методів навчання. Обґрунтовано необхідність модернізації фізичного виховання шляхом упровадження цифрових платформ, фітнес-додатків, технологій дистанційного та змішаного навчання, а також засобів штучного інтелекту. Встановлено, що цифровізація сприяє індивідуалізації навчання, підвищенню мотивації студентів та формуванню здоров’язбережувальної компетентності. Виявлено основні проблеми та визначено напрями подальшого розвитку дисципліни в умовах цифрового освітнього середовища. /// EN: The article examines the peculiarities of transforming the content of the discipline «Physical Education» in the context of the digitalization of higher education. Modern approaches to the integration of digital technologies into the educational process are analyzed, and their impact on changes in the goals, content, forms, and methods of teaching is determined. The necessity of modernizing physical education through the implementation of digital platforms, fitness applications, distance and blended learning technologies, as well as artificial intelligence tools, is substantiated. It has been established that digitalization contributes to the individualization of learning, increases students’ motivation, and promotes the formation of health-preserving competence. The main problems are identified, and directions for the further development of the discipline in the conditions of a digital educational environment are outlined.
Transformation of the content of the discipline «Physical Education» in the context of digitalization of higher education
Keywords: фізичне виховання; цифровізація; вища освіта; цифрові технології; дистанційне навчання; здоров’язбережувальна компетентність; фітнес-технології; цифрове освітнє середовище; physical education; digitalization; higher education; digital technologies; distance learning; health-preserving competence; fitness technologies; digital educational environment